Half a century of South African "Border War" literature: a historiographical exploration - Wessels, Andre (Faculty of Humanities, University of the Free State, 2017)
Half a century ago, in 1966, the so-called “Border War” broke out in what was then called South-West Africa (SWA) – known as Namibia after gaining independence in 1990. It was the most comprehensive, costly and traumatic of all the apartheid wars, and although it focused on SWA/Namibia, the conflict spilled over into Angola and Zambia, and should also be viewed in relation to the role played by the then South African Defence Force (SADF) in Rhodesia/Zimbabwe and in Mozambique. While the War for Southern Africa (1966-1989) was being fought, a number of books on the conflict were published. In the 1990s, while South Africa experienced a decade of dramatic political changes and concomitant transformation, not many books on the war “up north” and “on the border” were published, but from about the dawn of the new millennium, there has been a steady stream of publications (mostly in South Africa) that deal with the abovementioned conflict. Why this renewed interest? Who are the authors? What do they write about? This article endeavours to provide answers to these and related questions by analysing half a century of “Border War” literature, primarily focusing on books published in South Africa. The way in which these publications can influence people and thus, also the extent to which the legacy of the apartheid era is continued, will also be addressed. For obvious reasons, the issue of memory and violence, the legacies of trauma, the legacies of conscription, and the challenges with regard to researching the apartheid wars, as well as related matters, will also be interrogated.
Keywords: Border War; Military history; Namibia; Angola; South African literature; National service/conscription; War memoirs; South African Defence Force